REINFORCEMENT PENDIDIKAN AGAMA ISLAM PADA MAHASISWA MELALUI PROGRAM KEGIATAN MULTIKULTURAL DI UNIVERSITAS YUDHARTA PASURUAN - Ning Sulianah; Askhabul Kirom; Achmad Yusuf (Journal Multicultural of Islamic Education, 2023)
Yudharta Pasuruan University is one of the institutions of higher education in which there are not only students or lecturers who are Muslim, but there are also some Christians and Catholics. So that there is a need for Reinforcement of Islamic Education in Students Through Multicultural Activities Program.This study uses qualitative methods with phenomenology techniques and the data collection technique was done with three techniques, namely interview, observation and documentation. The types and sources of data in this research are: 1) Primary data and 2) Secondary data. The data analysis technique used by researchers is to use three data acquisition procedures, namely: 1. Data Reduction (Data Reduction). 2. Data Presentation/ Display. 3. Data Verification. Validity is done by triangulation of sources and techniques.The results of this study include: 1. Multicultural activities: Psychology Student Association of the University of Yudharta Pasuruan (Himapsi UYP) holding Psychofun Education, Head of Postgraduate UYP, Filling in Speech at the 2021 Christmas and New Year Celebration, Yudharta Held Coffee with Defending the Country, Program Students Arabic Studies Conducted Field Studies at GKJW Pandaan.2. The process of verbal reinforcement through multicultural activities and non-verbally through the building of the 4-pillar monument, the four pillars of the University of Yudharta Pasuruan, namely Pancasila, the UUD 1945,NKRI, and Bhinneka Tunggal Ika and the inscription of the world community's peace pledge. 3. The impact of Islamic Education Reinforcement on students through Multicultural activities at the University of Yudharta Pasuruan makes students have an attitude of tolerance, an attitude of cooperation, and an attitude of social care.